Progressive inelastic deformation of a girth-welded stainless steel pipe under internal pressure and cyclic bending. (1st December 2016) - Bae, Wan-Gon; Chang, Kyong-Ho; Lee, Chin-Hyung
Abstract: This study aims to characterize numerically the ratcheting behavior of a girth-welded straight stainless steel pipe in combined action of internal pressure and cyclic bending loading. Finite element (FE) thermal simulation of the girth butt welding process is first performed to identify weld-induced residual stresses. Three-dimensional (3-D) elastic-plastic FE analyses incorporated with the cyclic plasticity constitutive model capable of describing the cyclic plastic performance are next conducted to scrutinize the local (circumferential strain) and global (cross-section diameter change) ratcheting responses of the girth-welded stainless steel pipe under internal pressure and cyclic bending, which take the residual stresses and plastic strains obtained from the preceding thermal simulation as the initial condition. The analytical results demonstrate that welding residual stresses in combination with the internal pressure have significant effects on the hoop strain rate and the in-plane and out-of-plane diameter changes, and the degree and shape of the ovalization which occurs during the multiaxial ratcheting are dependent on the applied loads. Highlights: Ratcheting behavior of a girth-welded pressurized stainless steel pipe in cyclic bending was analyzed. A cyclic plasticity constitutive model capable of simulating the cyclic responses was presented. 3-D elastic-plastic FE analyses incorporated with the constitutive model were performed. The local and global ratcheting responses under various loading conditions were scrutinized.